Contact lens hydrophobicity and roughness effects on bacterial adhesion - Giraldez, Maria J. (2010)
Purpose. This study was designed to assess whether hydrogel contact lens (CL) surface hydrophobicity and roughness affect Staphylococcus epidermidis adhesion. Methods. Bacterial adhesion experiments were performed on two unworn silicone hydrogel and three unworn conventional hydrogel CLs using the S. epidermidis strain CECT 4184. Microbial colonization was assessed by conducting counts expressed as colony-forming units. CL hydrophobicity was determined through water contact angle measurements and the roughness parameters such as mean surface roughness (Ra), kurtosis (Rku), and skewness (Rsk) were determined through atomic force microscopy in Tapping Mode. Results. The conventional CLs showed similar water contact angles (p <0.05) and were classified as hydrophilic. The silicone hydrogel CLs yielded hydrophobic contact angles with no significant differences between them (p< 0.05). The lenses with the highest (nelfilcon A and ocufilcon B) or lowest (comfilcon A and omafilcon A) Ra values displayed a lesser or greater extent of spikiness of their surfaces, respectively. All lenses showed a predominance of peaks (Rsk >0) over troughs. S. epidermidis adhered more to the hydrophobic CLs (p <0.05). Omafilcon A and comfilcon A, which showed the lowest Ra values among the hydrophilic and hydrophobic lenses, respectively, returned the lowest bacterial adhesion scores (p< 0.05). Conclusions. Our results suggest that more hydrophobic CLs are more prone to S. epidermidis adhesion. Although the Ra appears to be related to S. epidermidis adhesion, the influence of Rku and Rsk on this variable remains unclear.